ANALISIS PENGENDALIAN INTERN TERHADAP PERSEDIAAN BAHAN MAKANAN DI HOTEL MELIA BALI VILLAS & SPA RESORT - I Putu Arnawa (Institut Pariwisata dan Bisnis Internasional, 2014)
This Research is meant to know how observation system applied by Hotel Melia Bali Villas & Spa Resort to acceptance procedure, depository and expenditure of food-stuff. As for is technics of research the used Technics of Descriptif Comparability that is by comparing among existing theory with fact in execution of goodness at part of acceptance, depository, and expenditure of food-stuff. From result of this research find 1). The happening of deviation among theory with execution of goodness part of acceptance, depository, and part of outflow of goods or food-stuff, 2). Totally there are damage above 1% from specified tolerance range that is 1%. 3). Existence of deviation indication in good procedure at acceptance procedure, Depository and Outflow of goods or food-stuff, this matter because weakening of observation intern in each shares, so that cause the happening of damage of Food-Stuff which high enough. As for type deviation of procedure that happened are following : Less accurate to acceptance pursuant to Note Purchase Order, do not use Standard of Purchase Specification, Depository Method take no account of classification of materials, and Outflow of goods or food-stuff without Store Room Requesition and without method of FIFO which have been specified. So that generate damage of materials, so that cause purchasing anggagaran become to mount, sale of natural food of degradation, and advantage of ever greater company